Robust and highly reactive membranes for continuous disposal of chemical warfare agents: Effects of nanostructure and functionality in MOF and nanochitin aerogel composites - Seo, Jin Young; Song, Younghan; Lee, Jung-Hyun; Na, Jongbeom; Baek, Kyung-Youl (Pergamon Press Ltd., 2024)
Developing appropriate disposal of stockpiles of chemical warfare agents (CWAs) has gained significant attention as their lethal toxicity seriously harms humanity. In this study, a novel green-fabrication method with UiO-66 catalysts and amine-functionalized chitin nanofibers (ChNFs) was suggested to prepare durable and highly reactive membranes for decomposing chemical warfare agents (CWAs) in the continuous flow system. The strong interaction between ChNFs and the UiO-66 led to stable loading of the UiO-66 on the continuous nano-porous channel of the ChNF reactive membrane even with high loading of UiO-66 (70 wt% of UiO-66 in the ChNF substrate). In addition, the Bronsted base functionalities (-NH2 and -NHCOCH3) of the ChNF enhanced the catalytic activity and recyclability of the UiO-66. The resulting 70-ChNF composites can effectively decompose a nerve agent simulant (methyl paraoxon) even after 7 repeatable cycles, which has been not obtained in the previous UiO-66 catalyst. The ChNF/UiO-66 reactive membranes with 1 m2 of the area decomposed 130 g of CWAs within an hour in a continuous flow system. We believe these robust and highly reactive membranes can provide a sustainable and efficient solution for the massive CWA disposal and also contribute to the advancement of functional membrane material science.